Thermal Stability and Inhibitory Action of Red Grape Skin Phytochemicals against Enzymes Associated with Metabolic Syndrome - Daniela Serea; Nina Nicoleta Condurache; Iuliana Aprodu; Oana Emilia Constantin; Gabriela-Elena Bahrim; Nicoleta Stănciuc; Silvius Stanciu; Gabriela Rapeanu (MDPI AG, 2022)
The present study focuses on heat-induced structural changes and the degradation kinetics of phytochemicals and antioxidant activity of red grape skin extract. The thermal degradation of anthocyanins, flavonoids, polyphenols, and antioxidant activity followed a first-order kinetic model, increasing with temperature due to the intensification of the degradation process. The activation energy (Ea) highlighted this phenomenon. Likewise, the kinetic and thermodynamic parameters certified the irreversible degradation of the bioactive compounds from the skin of the Băbească neagră grape variety. Both temperature and duration of heating had a significant impact on the content of bioactive compounds. In addition, the red grape skin extract inhibited certain enzymes such as α-amylase, α-glucosidase, lipase, and lipoxygenase, which are associated with metabolic syndrome and inflammation. Further knowledge on the possible inhibition mechanisms exerted by the major anthocyanins found in red grape skin extract on the metabolic syndrome-associated enzymes was gathered upon running molecular docking tests. Detailed analysis of the resulting molecular models revealed that malvidin 3-O-glucoside binds in the vicinity of the catalytic site of α-amylase and lipase, whereas no direct contact with catalytic amino acids was identified in the case of α-glucosidase and lipoxygenase.